2000
DOI: 10.1152/ajpregu.2000.279.3.r925
|View full text |Cite
|
Sign up to set email alerts
|

Membrane mechanisms for electrogenic Na+-independentl-alanine transport in the lizard duodenal mucosa

Abstract: The active Na(+)-independent transport of L-alanine across the duodenal mucosa of the lizard Gallotia galloti was studied in Ussing-type chambers using a computer-controlled voltage clamp. Addition of L-alanine to the Na(+)-free bathing solutions resulted in a significant L-alanine absorption (J(net)) that was paralleled by an increase in transepithelial short-circuit current (I(sc)) and potential difference (PD) without apparent changes in the tissue conductance. The concentration dependence of J(net), PD, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…For neutral amino acids, the existence of systems that transport [NBB system (neutral brush border system, transports most neutral amino acids but excludes MeAIB); system A; system ASC; Phe system (primarily phenylalanine, glycine, and methionine); ␤-amino (␤-amino acids such as taurine and ␤-alanine); Imino (imino acids such as proline, hydroxyproline); and the Na ϩ -independent system L] have been reported in isolated cells or membrane vesicles obtained from the small intestine of different species of mammals (11,19,30). Recently, we have demonstrated the presence both of Na ϩ -dependent and -independent active-transport mechanisms for L-alanine in the duodenum of the lizard Gallotia galloti (13).…”
mentioning
confidence: 99%
“…For neutral amino acids, the existence of systems that transport [NBB system (neutral brush border system, transports most neutral amino acids but excludes MeAIB); system A; system ASC; Phe system (primarily phenylalanine, glycine, and methionine); ␤-amino (␤-amino acids such as taurine and ␤-alanine); Imino (imino acids such as proline, hydroxyproline); and the Na ϩ -independent system L] have been reported in isolated cells or membrane vesicles obtained from the small intestine of different species of mammals (11,19,30). Recently, we have demonstrated the presence both of Na ϩ -dependent and -independent active-transport mechanisms for L-alanine in the duodenum of the lizard Gallotia galloti (13).…”
mentioning
confidence: 99%
“…This conclusion is supported by our data of unchanged unilateral fluxes from the serosal compartment. Using electrophysiological and radiotracer techniques, we have recently demonstrated that active L-alanine transport across the lizard duodenum could be explained by the simultaneous operation of different carriers (Díaz et al, 2000;Medina et al, 2001). These distinct transport pathways could be resolved on the basis of their different Na + dependence, substrate affinity, kinetic features and electrical properties.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that, under short-circuit conditions, the overall L-alanine transport in the lizard duodenum could be completely explained by the simultaneous participation of two Na + -dependent transport systems, endowed with properties of systems ASC and A, plus one Na + -independent electrogenic carrier (Díaz et al, 2000;Medina et al, 2001). These three different transport systems could be individually dissected by means of a strategy based on the differential substrate affinities and sodium dependence.…”
Section: Effects Of Db-camp and A23187 On Individual L-alanine Transpmentioning
confidence: 99%
See 2 more Smart Citations